Erasing of an optically induced grating in a semi-insulating multiple quantum well waveguide - Weinert-Rączka, Ewa; Wichtowski, Marek (Photonics Letters of Poland, 2012)
An interaction between optical signal guided in a photorefractive multiple quantum well planar waveguide and two external waves is considered. The external waves create a refractive index grating in the waveguide core which can be applied for frequency selective switching of guided signals. The influence of free carriers generated by the signal wave on the stability of photorefractive grating is analyzed. Full Text: PDF References D.D. Nolte, "Semi-insulating semiconductor heterostructures: Optoelectronic properties and applications", [CrossRef] M. Wichtowski, A. Ziółkowski, E. Weinert-Rączka, "A general approach to the space–charge field solution in photorefractive materials in a TWM geometry", J. Opt. 12, 065201 (2010)[CrossRef] E. Weinert-Rączka, M. Wichtowski, A. Ziółkowski, G. Staroń, "Photorefractive Grating in Multiple Quantum Well Planar Waveguide", Acta Phys. Pol. A 103, 229 (2003) A. Ziółkowski, E. Weinert-Rączka, "Dark screening solitons in multiple quantum well planar waveguide", [CrossRef] A. Ziółkowski, "Temporal analysis of solitons in photorefractive semiconductors", J. Opt. 14, 035202 (2012)[CrossRef] M. Wichtowski, E. Weinert-Rączka, "Photorefractive Multiple Quantum Well Waveguide as a Bragg Reflector ", Acta Physica Polonica A 103, 239 (2003) Q. Wang, R. M. Brubaker, D. D. Nolte and M. R. Melloch, "Photorefractive quantum wells: transverse Franz—Keldysh geometry", J. Opt. Soc. Am. B 9, 1626 (1992)[CrossRef] D. D. Nolte, D. H. Olson, G. E. Doran, W. H. Knox, A. M. Glass, "Resonant photodiffractive effect in semi-insulating multiple quantum wells", A.M. Glass. J. Opt. Soc. Am. B 7, 2217 (1990)[CrossRef] D.D. Nolte, M. R. Melloch : In: Photorectractive effects and Materials, ed. by D. D. Nolte (Kluwer, Dordrecht 1995) L. F. Magaňa, F. Agulló-López and M. Carrascosa, "Role of physical parameters on the photorefractive performance of semiconductor multiple quantum wells", J. Opt. Soc. Am. B 11, 1651 (1994)[CrossRef] Q. Wang, R. M. Brubaker, D. D. Nolte, "Photorefractive phase shift induced by hot-electron transport: multiple-quantum-well structures", J. Opt. Soc. Am. B 9, 1773 (1994)[CrossRef] P. Vaveliuk, B. Ruiz, N. Bolognini, "Analysis of the steady-state photorefractive harmonic gratings", Phys. Rev. B, 59, 10985 (1999)[CrossRef] D. S. Chemla, D. A. B. Miller, P. W. Smith, A. C. Gossard, W. Wiegmann, "Room temperature excitonic nonlinear absorption and refraction in GaAs/AlGaAs multiple quantum well structures", IEEE J. Quantum. Electron. 20, 265 (1984)[CrossRef] D.D. Nolte, Q. Wang, "Robust infrared gratings in photorefractive quantum wells generated by an above-band-gap laser", Appl. Phys Lett. 58, 2067 (1991)[CrossRef]